2014
DOI: 10.1002/jcla.21774
|View full text |Cite
|
Sign up to set email alerts
|

Marked Elevation of Excitatory Amino Acids in Cerebrospinal Fluid Obtained From Patients With Rotavirus‐Associated Encephalopathy

Abstract: Rotavirus is the most common cause of severe gastroenteritis in young children; however, its pathogenesis and immunity are not completely understood. Even less well recognized is rotavirus-induced central nervous system (CNS) involvement, which has been associated with seizure, encephalopathy and death, among others. To elucidate the host response to rotavirus infection, we retrospectively examined neurotransmitter amino acids in the cerebrospinal fluid (CSF) of 19 children with CNS involvement associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our results support previous studies linking rotavirus-induced autoimmunity to arthritis, vasculitis, and neurologic diseases . Previous studies indicated that rotavirus infection could potentially trigger autoimmunity in immune-privileged sites, including the intestine, pancreas, brain, kidney, and lymph nodes .…”
Section: Discussionsupporting
confidence: 92%
“…Our results support previous studies linking rotavirus-induced autoimmunity to arthritis, vasculitis, and neurologic diseases . Previous studies indicated that rotavirus infection could potentially trigger autoimmunity in immune-privileged sites, including the intestine, pancreas, brain, kidney, and lymph nodes .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it was recently demonstrated that the concentration of neurotransmitter amino acids (i.e., glutamate, glycine, and taurine) in the CSF of children with RV infection and CNS involvement were significantly higher in patients who had experienced prolonged seizures with encephalopathy than in those with CwG. 47 On the contrary, the hypothesis that particular RV genotypes could be the cause of CwG is debated. Choi et al detected the P 4 G2 genotype at a higher frequency than other genotypes in children with CwG.…”
Section: Factorsmentioning
confidence: 98%
“…116) A clinical study showed that, in 19 children with CNS involvement associated with rotavirus infection, excitatory neurotransmitter levels (glutamate, glycine, and taurine) in the CSF were higher in patients with prolonged seizures accompanied by encephalopathy than in patients with a brief cluster of seizures without encephalopathy. 117) As mentioned earlier, viral encephalitis tends to demonstrate asymmetrical focal lesions on MRI as in herpes simplex virus encephalitis, while rotavirus-associated encephalopathy is generally characterized by bilateral symmetry, the predilection of cerebral white matter including the corpus callosum, and the lesions are well-demarcated, particularly on DWI.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 91%
“…A previous report showed elevated PGE2 and PGF2 levels in the plasma and stool of rotavirus-infected children [ 116 ]. A clinical study showed that, in 19 children with CNS involvement associated with rotavirus infection, excitatory neurotransmitter levels (glutamate, glycine, and taurine) in the CSF were higher in patients with prolonged seizures accompanied by encephalopathy than in patients with a brief cluster of seizures without encephalopathy [ 117 ].…”
Section: Proposed Potential Mechanisms Of Rotavirus Infection-associa...mentioning
confidence: 99%